2014
DOI: 10.1179/2295333714y.0000000110
|View full text |Cite
|
Sign up to set email alerts
|

A case of delayed oxaliplatin-induced pseudo-obstruction: an atypical presentation of oxaliplatin neurotoxicity

Abstract: Chemotherapy-induced neurotoxicity is a serious complication of cancer treatment. Oxaliplatin, a third-generation platinum drug, has become one of the first-line therapies used in the treatment of metastatic colorectal cancer. Peripheral neuropathy is a common complication of platinum-based chemotherapy. Most commonly a sensory neuropathy occurs with cold-triggered symptoms in the acute phase and numbness and painful paresthesias as a late presentation. Autonomic neurotoxicity and late presentation, months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Oxaliplatin is an important anti-cancer drug in clinical use [ 1 , 2 ]. Studies have shown that the RIP1siRNA could enhance the oral cancer cell KB apoptosis induced by oxaliplatin [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxaliplatin is an important anti-cancer drug in clinical use [ 1 , 2 ]. Studies have shown that the RIP1siRNA could enhance the oral cancer cell KB apoptosis induced by oxaliplatin [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin is a crucial chemotherapy drug that plays an important role in colorectal cancer and oral cancer treatment. However, the molecular mechanism of oxaliplatin in killing tongue squamous cancer cells is still unknown [ 1 , 2 ]. Previous studies demonstrated that oxaliplatin could kill cancer cells through induction of apoptosis of tongue squamous cells [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these findings support the idea of a role for FKBP51 in the EMT process in CRC. Interestingly, in CRC tissue sections, several cells of the myenteric plexus were strongly positive (Article 2, Fig.1B), while in healthy colon the signal was fainter (Article 2, Fig.B), suggesting a role for this immunophilin in the development of oxaliplatin-induced neuropathy [154]. IHC analyses allowed the observation of changes in FKBP51 expression levels and localization in malignant liver compared with CRC, confirming the downregulation of this immunophilin in metastasized liver sections resected after oxaliplatin-CT. ImageJ software, implemented with the open source plug-in IHC Profiler, was used to compare the visual human interpretation to that of the computer-aided vision.…”
Section: Oncol Lett Doi:103892/ol20176525mentioning
confidence: 98%
“…Assim, nucleófilos fracos tais como bicarbonatos de sangue ou de di-hidrogenofosfato intracelular deslocam o grupo oxalato (Cvitkovic, 1998;Fink et al, 1996), resultando na formação de intermediários instáveis que são facilmente hidrolizados para deslocar 1,2-DACH-platina. Esta última espécie é rapidamente convertida em monoaqua-1,2-DACH monochloroplatinum e 1,2-DACH, espécies de platina, que instantaneamente reagem com o DNA (Vandamme et al, 2014). (Gamelin, 2007;Sakurai et al, 2009 Quadro 3.…”
Section: Mecanismos De Açãounclassified